Analisis User Experience Aplikasi myBCA Menggunakan Metode User Experience Questionnaire (UEQ+) Dan Dampaknya Terhadap Perilaku Pengguna - Devi Indriyani; Reghina Masayu; Maulida Syifa (Journal of Information Systems and Business Technology, 2025)
This study aims to analyze the user experience of the MyBCA application obtained through the User Experience Questionnaire Plus and relate it to user behavior towards the use of digital banking services. This data was collected by distributing UEQ+ by creating a questionnaire and then sending it to active MyBCA users, which measures several aspects, such as usability, informativeness, efficiency, attractiveness, and trust, of the application used. The results of data processing show that most respondents gave high ratings, especially to the aspects of efficiency and trust, which help them feel relieved and simplify the digital transaction process. This study shows that there is a strong relationship between the quality of user experience and user behavior, and a positive user experience encourages the frequency of use and user attitudes. Overall, this study emphasizes that improving user experience can be an important strategy for developers in strengthening the adoption of digital banking services.